SMART Partnerships: Strategies to Support Academic-Clinical Nurse Collaborations in Behavioral Intervention Studies - Hendricks-Ferguson, Verna L. (Clin Nurse Spec, 2017)
Evidence-based nursing is in the forefront of health care delivery systems. Federal and state agencies, academic institutions, and health care delivery systems recognize the importance of nursing research. This article describes mechanisms that facilitate nursing partnerships yielding high level research outcomes in a clinical setting. A phase II multi-center behavioral intervention study with pediatric stem cell transplant patients was the context of this academic/clinical research partnership. Strategies to develop and maintain this partnership involved a thorough understanding of each nurse’s focus and barriers. A variety of communication plans and training events maximized pre-existing professional networks. Academic/clinical nurses’ discussions identified barriers to the research process, the most significant being role conflict. Communication and validation of benefits to each individual and institution facilitated the research process during challenging times. Establishing strong academic/clinical partnerships should lead to evidence-based research outcomes for the nursing profession, healthcare delivery systems, and patients and families.